Manual on Statistics of International Trade in Services 2010 Compiler's Guide - United Nations Department of Economic; Social Affairs (United Nations, 2017)
The Guide provides practical support on the compilation of service transactions between residents—non-residents transactions utilizing the EBOPS classification with special emphasis on the partner country break-down, the foreign affiliates statistics (FATS) and also on flows by modes of supply. The overarching aim is to increase the availability and quality of SITS in order to fulfil the urgent needs and demands for such data by policy makers, researchers, market analysts and the public in general. While the international standards in economic statistics are in the process of being implemented, this Guide comes timely, providing the statistical community with guidelines, best practices, case studies, and practical advice on the compilation of SITS.